Starch-glyceryl monostearate edible coatings formulated with sodium benzoate control postharvest citrus diseases caused by Penicillium digitatum and Penicillium italicum - SOTO-MUÑOZ, Lourdes; MARTÍNEZ-BLAY, Victoria; PÉREZ-GAGO, María B.; FERNÁNDEZ-CATALÁN, Asunción; ARGENTE-SANCHIS, Maricruz; PALOU, Lluís (Phytopathologia Mediterranea, 2021)
The curative antifungal activity of edible composite coatings (ECs) based on pregelatinized potato starch-glyceryl monostearate (PPS-GMS) formulated with or without sodium benzoate (SB) to control green mould (caused by Penicillium digitatum) and blue mould (P. italicum) was assessed on ‘Orri’ mandarins, ‘Valencia’ oranges and ‘Fino’ lemons. These fruit were artificially inoculated with P. digitatum or P. italicum, treated by immersion in coating emulsions and compared to uncoated control fruit immersed in water and fruit immersed in 2% SB (w/v) aqueous solution. Treated fruit were then stored at either 20°C or commercial low temperature (5°C for mandarins and oranges, 12°C for lemons). Coatings without SB did not exhibit antifungal activity, whereas coatings containing 2% SB reduced incidence and severity of green and blue moulds, in comparison to the controls, on all citrus species and in all storage conditions, without differing from the aplication of 2% SB alone. For example, incidence reduction on ‘Fino’ lemons was from 99 to 0% after 7 d at 20°C, and from 99 to 30% after 2 weeks at 12°C. None of the treatments was phytotoxic. These results indicate that applications of SB as antifungal ingredient of PPS-GMS based ECs is a promising non-polluting alternative to control Penicillium postharvest decay of citrus, and these ECs are effective substitutes for conventional waxes amended with synthetic fungicides.